Determination of Cost of Illness of Type 2 Diabetes Mellitus in Tertiary Care Setting - Adiga, Usha; Adiga, Sachidananda; Rai, Tirthal (Technological Innovation in Pharmaceutical Research Vol. 11, 2021)
Diabetes mellitus imposes a considerable burden on health systems and societies. The cost implications of diabetes to society are multifold: direct costs to people with diabetes, their families and to the health care sectors, indirect costs to society and government, which are the productivity costs; and intangible costs, which means adverse effects on quality of life. Very little is known about the economic impact of diabetes in the developing world where predicted increases in prevalence are highest. The total annual medical costs is significantly higher in complicated diabetics as compared to those without complications. Awareness creation on primary and secondary prevention of diabetes and its complications is the need of the hour, alongside capacity strengthening of medical and paramedical professionals involved in diabetes care.